If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(6x-3)=2(12x-6)
We move all terms to the left:
4(6x-3)-(2(12x-6))=0
We multiply parentheses
24x-(2(12x-6))-12=0
We calculate terms in parentheses: -(2(12x-6)), so:We get rid of parentheses
2(12x-6)
We multiply parentheses
24x-12
Back to the equation:
-(24x-12)
24x-24x+12-12=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 1/2(14+x)=-8(6-x) | | s/4.8=30.6/28.8 | | 2x-3+x=-x+9 | | -x+(-8)=-7 | | 122=8x+2 | | 63-3y=6y | | 5x+15=2x+3x+2 | | 5x/2-x=x/10-15/5 | | 94=-19x+22x | | Y=-25x+5/6 | | 5x+12+2x=8+7x | | 17w=9w+32 | | 6x–3+5x=13x-19 | | 9=y+(-4) | | 17+b=36 | | 3(4z+4)=36 | | -2(x-14)=-38 | | -2x+4=6-2x | | -6x-2x=16+2x-2x | | -9=7x+11 | | -6=-16+2x | | 0.5y=17’ | | 4.3x+8.4x=1.6+-0.9= | | 9•(4-6x)+(3-5x)=-20 | | 940=-16x²+1800 | | -6=-16+.2z | | 200-6x+80x-750=180 | | 11z-55=33 | | 228=155-x | | 4z-8+z=-73 | | 7x+1=185 | | 7/2(3x-8)=35 |